Iowa CBC reporting form, Fort Dodge, December 28, 1985 - Kuhlman, Maryet al (1985)
Checklist dated December 28, 1985 compiled by Mary Kuhlman. A list of birds sighted by Kuhlman and fourteen others around Fort Dodge. A total of 29 species and 1,458 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed